Narcissism and Entitlement in Millennials: The Mediating Influence of Community Service Self Efficacy on Engagement. (October 2016) - Credo, Keith R.; Lanier, Patricia A.; Matherne, Curtis F.; Cox, Susie S.
Abstract: There is a rapidly growing body of research on the more negative aspects of the expanding millennial population. Alternatively, the current study explores possible benefits resulting from millennial traits typically considered to be negative, specifically entitlement and narcissism. The authors hypothesize that self-efficacy generated by the creation of service opportunities, may not only improve engagement, but may also lessen the influence of negative millennial traits including entitlement and narcissism. Hypotheses were explored using a sample of 239 millennials. Following Preacher and Hayes' (2008) method for mediation, we found that the model tested was fully mediated. Results and discussion follow. Highlights: Findings indicate a possible negative relationship between narcissism and engagement. Psychological entitlement as measured may not influence engagement in millennials. Community service self-efficacy mediated the relationship between narcissism and engagement. Participation in service activities may lessen the influence of narcissism in millennials.